1978
DOI: 10.1104/pp.61.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Root Anaerobiosis on Ethylene Production, Epinasty, and Growth of Tomato Plants

Abstract: Experiments were performed to determine the source(s) of ethylenecausing epinasty in flooded tomato plats (Lyc_perskoa escultm MilL). Simultaneous measurements were made of ethylene synthesized by the roots and shoots of tomato plants exposed to This study tested these hypotheses by using N2 ventilation of the root zone, rather than flood water, to impose an 02 deficiency upon the root without blocking gas diffusion. Microbial contribution of ethylene was prevented by using inert growing media. A special app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
41
1
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 16 publications
2
41
1
1
Order By: Relevance
“…When wounded by excision, tissues of both dgt and VFN8 produced a burst of "stress ethylene." These observations suggest that IAA is not involved in the production of wound ethylene.Waterlogging is also known to increase ethylene synthesis in tomato (2,6). It has recently been demonstrated that the stimulation of ethylene synthesis in waterlogged plants is due to export of an ethylene precursor, ACC2, from anaerobic roots (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When wounded by excision, tissues of both dgt and VFN8 produced a burst of "stress ethylene." These observations suggest that IAA is not involved in the production of wound ethylene.Waterlogging is also known to increase ethylene synthesis in tomato (2,6). It has recently been demonstrated that the stimulation of ethylene synthesis in waterlogged plants is due to export of an ethylene precursor, ACC2, from anaerobic roots (3).…”
mentioning
confidence: 99%
“…Waterlogging is also known to increase ethylene synthesis in tomato (2,6). It has recently been demonstrated that the stimulation of ethylene synthesis in waterlogged plants is due to export of an ethylene precursor, ACC2, from anaerobic roots (3).…”
mentioning
confidence: 99%
“…The high production and accumulation of ethylene in shoots results from the high ACC levels, synthesized in roots by ACC synthase, then transported from the root system to shoot where it is converted to ethylene by ACC oxidase (Bradford et al 1982). Since oxygen concentrations of waterlogged root systems are too low or nonexistent, the conversion of ACC to ethylene by ACC oxidase cannot take place (Jackson and Campbell 1976;Bradford and Dilley 1978;Wang and Arteca 1992;Banga et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Waterlogging been reported to cause elevated ethylene levels and epinasty in the shoot regardless of whether the condition is imposed by waterlogging or by flushing with N2 (4,12,14). It has been shown that ethylene production by maize (Zea mays L.) roots exposed to 5 kPa oxygen was inhibited by AVG supplemented to the nutrient solution and this also reduced aerenchyma formation (13).…”
Section: Introductionmentioning
confidence: 99%
“…Under aeration, AOA stimulated ACC synthase activity in both the roots and leaves. However, in combination with low 02 conditions, AOA caused a stimulation in ACC synthase activity in the leaves and no effect in the roots.Ethylene production is observed in all higher plants, where it is involved in numerous aspects of plant growth and development but most notably as a response to stress conditions (1).Waterlogging been reported to cause elevated ethylene levels and epinasty in the shoot regardless of whether the condition is imposed by waterlogging or by flushing with N2 (4,12,14). It has been shown that ethylene production by maize (Zea mays L.) roots exposed to 5 kPa oxygen was inhibited by AVG supplemented to the nutrient solution and this also reduced aerenchyma formation (13).…”
mentioning
confidence: 99%